Ladies in lavender [videorecording (DVD)] - Dance, Charles; Dance, Charles; Dench, Judi, 1934-; Smith, Maggie, 1934-2024 (Sony Pictures Home Entertainment, 2005)
The peaceful life of two aging sisters is shattered when they take in a young Polish violinist who they find injured after having been washed ashore near their coastal English home. Their town is suspicious of any visitors and things get worse when he befriends a Russian woman who is visiting the town.